New data on flying fox species (Pteropus spp.) in Vietnam - Thong, Vu Dinh (Academia Journal of Biology, 2015)
To date, three species of Pteropus have been recorded in Vietnam, including Small Flying Fox Pteropus hypomelanus, Lyle’s Flying Fox Pteropus lylei and Large Flying Fox Pteropus vamyrus. P. hypomelanus was recorded at Conson island in 1869, followed by Lyle’s Flying Fox in Saigon (Giadinh former province in 1908) and then Large Flying Fox at Phuquoc island and Thuathien-Hue province. For some subsequent decades, the information on these species, especially the Flying Foxes, was completely limited. Since 2001, a large number of detailed surveys on the bat fauna of Vietnam have been conducted through out the country, including the areas where the Flying Foxes were previously recorded. The surveys indicate that these species have been undergoing a decreased in number, because of different potential threats such habitat loss, hunting etc. It is probably warned that these species would be ones of the first mammals of Vietnam which could become extinct, unless the influential factors were urgently minimised and prevented. Based on the recorded data, characteristics of these species, which might deserve to be listed in the Red Data Book for Vietnam in next editions, are described.